Impact of Minor Gynecological Complications on Quality of Life. A Hospital-Based Observational Study - AYESHA GHAZANFAR,; MAHAM SHAUKAT,; AQEEDAT SHAHZAD,; AREEJ KHALID,; NAEEM, USAMA BIN (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Mild gynecological issues, including vaginal discharge, dysmenorrhea, pelvic pain, urinary symptoms, and irregularities in menstruation are very common in women, but the effect of such issues on the quality of life has not been given due consideration. This burden has to be understood to enhance clinical care and patient well-being. Objective: To evaluate how minor gynecological complications affect the quality of life of the patients who visit a tertiary care hospital. Methods: This was an observational study at this hospital, with 100 women between the ages of 18 and 55 years who presented with minor gynecological issues. Clinical assessment, gynecological assessment and investigations were conducted. The WHOQOL-BREF questionnaire was used to determine the quality of life in the physical, psychological, social and environmental domains. Data were processed with the help of SPSS 25, and the comparison of the mean QoL scores was conducted with the help of the various types of complaints and the period of the symptom occurrence in years. Results: The reason that most presented was the abnormal vaginal discharge (34 percent), dysmenorrhea (22 percent), pelvic discomfort (18 percent), urinary symptoms (14 percent), and the menstrual irregularities (12 percent). The women who experienced vaginal discharge and pelvic pain scored significantly lower on physical and psychological QoL. The number of symptoms was significantly correlated with impairment and those who reported more than 6 months had significantly lower QoL in all domains. Conclusion: Recommendation Small gynecological complications have a severe impact on the quality of life of women, in particular, in case of chronic or repeated symptoms. Raising early awareness, prompt treatment and extensive counseling of the patient will assist in lowering the total burden and enhancing wellbeing.